Radiofrequency ablation with or without transarterial chemoembolization for hepatocellular carcinoma meeting Milan criteria: a focus on tumor progression and recurrence patterns - Xie, Yong; Lyu, Tianshi; Guan, Haitao; Cao, Shoujin; Song, Li; Tong, Xiaoqiang; Zou, Yinghua; Wang, Jian (Frontiers in Oncology, 2024)
Background/objective The aim of this study was to evaluate tumor progression and recurrence patterns of radiofrequency ablation (RFA) with or without transarterial chemoembolization (TACE) for treating hepatocellular carcinoma (HCC) that meets Milan criteria. Methods This retrospective study included consecutive HCC patients meeting Milan criteria who underwent percutaneous RFA with or without TACE as initial treatment at a tertiary academic center between December 2017 and 2022. Technical success rate, local recurrence-free survival (LRFS), progression-free survival (PFS) and recurrence patterns were recorded. Results A total of 135 HCC patients (109 male [80.7%]) with a mean age of 62 years and 147 target lesions were retrospectively enrolled. The technical success rate was 99.3%. The median LRFS was 60 months, and the cumulative 1-, 3-, and 5-year LRFS were 88.9%, 70.1%, and 30.0%, respectively. Additionally, the median PFS was 23 months, with cumulative 1-, 3-, and 5-year PFS of 74%, 30%, and 0%, respectively. Multivariate analysis confirmed that age > 60, alpha-fetoprotein (AFP) (> 10), and albumin were associated with PFS (2.34, p = 0.004; 1.96, p = 0.021; 0.94, p = 0.007, respectively). Six recurrence patterns were identified: local tumor progression (LTP) alone (n = 15, 25.0%), intrahepatic distant recurrence (IDR) alone (n = 34, 56.7%), extrahepatic recurrence (ER) alone (n = 2, 3.3%), IDR + ER (n = 2, 3.3%), LTP + IDR (n = 5, 8.8%), and LTP + IDR + ER (n = 2, 3.3%). IDR occurred most frequently as a sign of good local treatment. Conclusions RFA in combination with TACE does not appear to provide an advantage over RFA alone in improving tumor progression in patients with HCC meeting the Milan criteria. However, further prospective studies are needed to confirm these findings and to determine the optimal treatment approach for this patient population.